(untitled) (Bangladesh Journal of Medical Microbiology, 2025)
Background: Prevalence of Extended-spectrum ß-lactamases (ESBL) producing uropathogenic strains have been found to be increased rapidly across the world including Bangladesh. Objective: This study was aimed to presents phenotypic and molecular characterization of ESBL producing Enterobacteriaceae and their antibiogram profile isolated from UTI patients of six different districts of Bangladesh. Methodology: This cross-sectional study was conducted in Microbiology Laboratory of BIRDEM general hospital, Dhaka, Bangladesh with 187 culture positive cases collected from six laboratories of Feni, Faridpur, Kishoreganj, Sirajganj, Shatkhira and Brahmanbaria during the period from September, 2018 to August, 2019 for one year. Different members of Enterobacteriaceae were isolated and susceptibilities of these isolates to 17 different antimicrobial agents were determined. Ceftazidime (CAZ), cefotaxime (CTX), ceftriaxone (CRO) and amoxiclave (AMC) were used for confirmation of ESBL producing isolates in Double Disc Synergy Test (DDST). Frequency of blaCTX-M, blaTEM and blaSHV among these isolates were further detected in this study. Results: Out of 187 culture positive cases, 171 samples were Enterobacteriaceae including Escherichia coli, Klebsiella species, Enterobacter species and Proteus mirabilis. Among them, 85 isolates were screened to be ESBLs producing Enterobacteriaceae and 52 isolates were confirmed as ESBL isolates in DDST. MIC of ceftazidime and MIC reduction of ceftazidime-clavulanic acid for confirmed ESBL producers was found ranged from 0.125ug/ml to 64ug/ml and 0.0156ug/ml to 32ug/ml respectively. Among 52 ESBL isolates, the blaCTX-M (86.3%) gene was predominant followed by blaSHV (22.7%) and blaTEM (18.2%) in ESBLs producing E. coli. All three bla genes were harboured in 2.3% and blaCTX-M+SHV were in 18.2% E. coli. Conclusion: Alarmingly increasing spread of single gene type blaCTX-M and blaSHV harboring multidrug-resistant ESBL producing Enterobacteriaceae in six district regions of Bangladesh emphasize ESBL detection routinely in all microbiology laboratories by DDST as rapid and cost-effective method and development of rational use of antibiotic strategies in UTI to control spread of ESBL production in community of Bangladesh. Bangladesh Journal of Medical Microbiology, January 2025;19 (1):60-69